Implementation of the Islamic Dirosah Program as a Foundation Curriculum for Students at MI Nurul Huda, Bengkulu City - Putri Surya Anita (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This study aims to describe the implementation of the Islamic Dirosah program as a foundation curriculum and the obstacles faced by schools in implementing the program and how schools overcome these obstacles. This type of research is field research, namely research conducted directly on a fact that occurs in the field. The design of the research is descriptive qualitative, the study will provide an empirical description of